Photo-oxidation products of α-pinene in coarse, fine and ultrafine aerosol: A new high sensitive HPLC-MS/MS method. (May 2018) - Feltracco, Matteo; Barbaro, Elena; Contini, Daniele; Zangrando, Roberta; Toscano, Giuseppa; Battistel, Dario; Barbante, Carlo; Gambaro, Andrea
Abstract: Oxidation products of α-pinene represent a fraction of organic matter in the environmental aerosol. α-pinene is one of most abundant monoterpenes released in the atmosphere by plants, located typically in boreal, temperate and tropical forests. This primary compound reacts with atmospheric oxidants, such as O3, O2, OH radicals and NOx, through the major tropospheric degradation pathway for many monoterpenes under typical atmospheric condition. Although several studies identified a series of by-products deriving from the α-pinene photo-oxidation in the atmosphere, such as pinic and cis-pinonic acid, the knowledge of the mechanism of this process is partially still lacking. Thus, the investigation of the distribution of these acids in the different size aerosol particles provides additional information on this regard. The aim of this study is twofold. First, we aim to improve the existing analytical methods for the determination of pinic and cis-pinonic acid in aerosol samples, especially in terms of analytical sensitivity and limits of detection (LOD) and quantification (LOQ). We even attempted to increase the knowledge of the α-pinene photo-oxidation processes by analysing, for the first time, the particle-size distribution up to nanoparticle level of pinic and cis-pinonic acid. The analysis of aerosol samples was carried out via high-performance liquid chromatography coupled to a triple quadrupole mass spectrometer. The instrumental LOD values of cis-pinonic and pinic acid are 1.6 and 1.2 ng L −1 while LOQ values are 5.4 and 4.1 ng L −1, respectively. Samples were collected by MOUDI II™ cascade impactor with twelve cut-sizes, from March to May 2016 in the urban area of Mestre-Venice (Italy). The range concentrations in the aerosol samples were from 0.1 to 0.9 ng m −3 for cis-pinonic acid and from 0.1 to 0.8 ng m −3 for pinic acid. Graphical abstract: Image 1 Highlights: A sensitive HPLC-MS/MS method was developed to quantify PM-bound cis-pinonic and pinic acids. Aerosol particle size distribution of cis-pinonic and pinic acids was evaluated. For the first time cis-pinonic and pinic acids were determined in the nanoparticles.